2003
DOI: 10.1182/blood-2003-06-1963
|View full text |Cite
|
Sign up to set email alerts
|

Lack of evidence for functional ADP-activated human P2X1 receptors supports a role for ATP during hemostasis and thrombosis

Abstract: Purine nucleotides acting through P2 receptors play key roles in platelet signaling. The P2X 1 receptor is an adenosine triphosphate (ATP)-gated ion channel that mediates a rapid calcium influx signal, but can also synergize with subsequent adenosine diphosphate (ADP)-evoked P2Y 1 receptormediated responses and thus may contribute to platelet activation during hemostasis. Recent studies have shown that P2X 1 receptors contribute to the formation of platelet thrombi, particularly under conditions of high shear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 24 publications
1
15
0
1
Order By: Relevance
“…Vial et al [109] have suggested that in vivo, these ATP-induced reactions could synergize with the platelet response to ADP through the P2Y 1 receptor and amplify the increase in intracellular calcium. Oury et al [110,111] obtained evidence for the importance in hemostasis of a synergy between ADP and ATP released from platelets stimulated by adherence to collagen.…”
Section: The P2x 1 Receptormentioning
confidence: 99%
“…Vial et al [109] have suggested that in vivo, these ATP-induced reactions could synergize with the platelet response to ADP through the P2Y 1 receptor and amplify the increase in intracellular calcium. Oury et al [110,111] obtained evidence for the importance in hemostasis of a synergy between ADP and ATP released from platelets stimulated by adherence to collagen.…”
Section: The P2x 1 Receptormentioning
confidence: 99%
“…ATP can affect thromboregulation and stimulate the immune cells responsible for asthma attacks (6,7 ). ATP has also been proposed as a mediator of vasodilation during ischemia, hypoxia, and exercise.…”
mentioning
confidence: 99%
“…В случае полного удаления ATP, восстановление этого рецептора происходит примерно за 5 мин [80]. Активация рецептора P2X 1 приводит к изменению формы тромбоцита, быстрой и обратимой централизации его секреторных гранул, однако агрегации тромбоцитов при этом не наблюдается [81,82]. Этот рецептор играет вспомогательную роль при активации тромбоцитов от коллагена, тромбина, ADP и TXA 2 .…”
Section: активация тромбоцитов при воздействии Atpunclassified